CHARACTERISTIC STUDY FOR THE HETEROGENEOUS ROLLING BEARING MATCH WAY - WU KaiSong; DENG Tao; CAI Can; FENG Yan (Jixie qiangdu)
When angular contact ball bearings match together,due to high demand of manufacturing and installation precision,only increasing the number of angular contact ball bearings to increase the radial bearing capacity has great limitations.Therefore,it was considered that using heterogeneous rolling bearing match to increase the radial bearing capacity of bearing match has obvious advantages.Structure characteristics and mechanical properties of the existing angular contact ball bearing match way has been analyzed and compared,and then the applicability of them has been explained.For the existence of the high accuracy requirement and the low radial load capacity,a way of heterogeneous rolling bearing match way was put forward.Its characteristic is to use deep groove ball bearings or cylindrical roller bearing to bear radial load bearing,and angular contact ball bearing to bear axial load.Then,the formula was derived for calculating the life of a heterogeneous rolling bearing match way.At the same time the life calculation formula of"QBC"angular contact ball bearing was deduced.Comparison of the two above show that heterogeneous rolling bearing match way obviously improves the radial bearing capacity,obviously prolong service life,and the demand of bearing manufacturing and installation accuracy is low.The results have been applied to an import petrochemical plant methylamine pumps.After calculation,heterogeneous rolling bearing match way increases by 52.5%.